Samba and the descent into violence in City of God. Issue 1 (1st April 2017) - Anselmo Hess, Hans Michael
The soundtrack analysis for Cidade de Deus (City of God) (2002) demonstrates how the 1960s Samba songs 'Alvorada' ('Dawn') and 'Preciso Me Encontrar' ('I Need to Find Myself') used in the film represent the samba lírico-amoroso and the depictions of rural living, idyllic favela, naivety and the hope and desire for a better life as well as a love for the romantic frustrations in the life of the malandro. As the story of the film moves into a new period and the favela descends into a world of drugs, violence and death, Samba changes its use and representational function in the film.